Barriers and facilitators to timely birth-dose vaccines in Kinshasa Province, the DRC: a qualitative study - Alix Boisson; Camille E. Morgan; Bruce Fried; Christopher M. Shea; Marcel Yotebieng; Patrick Ngimbi; Nana Mbonze; Kashamuka Mwandagalirwa; Pélagie Babakazo; Peyton Thompson (Journal of Global Health Reports)
# Background